IMPACT OF COVID-19 ON MIDDLE CHILDHOOD SOCIAL AND EMOTIONAL DEVELOPMENT: A NARRATIVE REVIEW WITH RECOMMENDATIONS - Salma, Umi (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
This study aims to narratively review various articles related to the social and emotional development problems of children affected by the COVID-19 pandemic and to find out preventive measures to keep children’s social and emotional development on track. The method used in this article is a review of articles related to the social and emotional development problems of children affected by the COVID-19 pandemic. The results of this study indicate that there are several problems related to social and emotional development in children during COVID-19 pandemic, namely anxiety, depression, attachment, annoyance, irritability, and fear of asking questions about the pandemic. The research also includes actions that can be taken to safeguard children's social and emotional development, such as community health education strategies and family support, managing games for children, physical activity, a balanced diet, regulating the use of gadgets, providing time to share sadness, providing time to listen to children, sharing feelings of security, strength, and affection with children, providing special care for children who suffer from toxic stress, provide psychosocial support, and provide initial psychological support.